Renal nuclear isotope study using dimercaptosuccinic acid in evaluating renal parenchymal changes in urinary tract infection in children - Ramachandrappa, Rajashekarmurthy G; Keshavamurthy, M L; Siddaraju, M L (Indian Journal of Child Health, 2016)
Background: Urinary tract infections (UTI) are among the most common diseases in childhood. The diagnosis and management of complicated UTI are difficult. The renal cortical scintigraphy using dimercaptosuccinic acid (DMSA) has been reported to be useful in children for confirmation of the diagnosis and for localization of parenchymal changes in acute pyelonephritis with renal scars. Objectives: To assess the role of 99m Tc-DMSA in identifying renal scars due to UTI in children. Materials and Methods: This study was a hospital-based prospective study conducted from November 2014 to October 2015. 53 children admitted with the first episode of the culture proven UTI. Children with vesicoureteric reflux or congenital renal anomalies were excluded from the study. All the patients were subjected to 99m Tc-DMSA. Results: An abnormal renal scan was observed in 28 out of 53 children (52.83%). The most common organism isolated was Escherichia coli (75.4%). All the children had fever (100%) followed by dysuria/increased frequency (50.94%). The majority of the renal parenchymal changes confined to the upper poles followed by lower poles and mid poles. Left kidney was involved more commonly (56%) than the right kidney (44%), whereas 3 children had bilateral involvement (10.71%). Parenchymal changes were common among children in 2-5 year age group (46.4%) followed by in children more than 5 years. Conclusion: DMSA renal scan has confirmed the high incidence of radiographically demonstrable renal scars in a significant number of children. It has helped to define parenchymal involvement in the form of pyelonephritic scars, the most common complication of UTI which is preventable.